Potential of rhizobacterial Pseudomonas and Bacillus spp. to manage papaya ringspot virus disease of papaya (Carica papaya (L.) - C. Ranasinghe; D. M. De Costa; B. M. V. S. Basnayake; D. M. Gunasekera; S. Priyadharshani; N. V. R. Navagamuwa (Tropical Agricultural Research, 2018)
The present study was conducted to determine the potential of rhizobacterial species in managing Papaya Ringspot Virus Disease (PRSVD) and their ability to promote plant growth and yield and induce host plant resistance through the activity of defense-related enzymes. Twenty Pseudomonas spp. and four Bacillus spp. which were isolated from healthy papaya rhizosphere were applied by two methods, namely seed treatment and a root dip. The ability to reduce symptom development, promote plant growth and yield along with synthesis of peroxidase, phenylalanine ammonia lyase (PAL) and β-1, 3- glucanase under plant house and field conditions were evaluated. Molecular identification confirmed the presence of P. fluorescens, P. putida, P. aeruginosa, P. taiwanensis and several unidentified species of Pseudomonas among the Pseudomonas isolates used in the present study. Application of six selected bacterial isolates either by seed or root dip method reduced leaf symptom severity and increased the activity of peroxidase and PAL enzymes significantly (P<0.005), compared to the plants which were not treated with bacterial isolates. When the bacterial isolates were applied by the root dip method, there was no significant (P<0.005) difference on the activity of peroxidase, PAL and β-1, 3- glucanase among the isolates. Results revealed the scattered ability of the rhizobacterial isolates to promote plant growth, reduce symptom development of PRSVD and induction of defense-related enzymes, though all the desirable features were not possessed by any given isolate. Hence, application of rhizobacterial mixtures is encouraged.